Perlindungan Pembeli Terhadap Kesalahan Harga Dalam Bisnis Ritel Modern - Nur Rizky Aulia Rahmah; Muhammad Amin; Ramadhani Alfin Habibi; Erry Fitrya Primadhany; Baihaki; Novita Mayasari Angelia; Muhammad Norhadi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The modern retail business is currently growing rapidly along with the times. Economic progress has also contributed to the development of the modern market and retail business in Indonesia. The modern retail business has now expanded to various cities in Indonesia. Even modern shops with minimarket franchises have spread to a number of cities and districts. Modern retail business in the form of hypermart, Indomaret, Alfamart, department store and wholesaler. While shopping centers can be in the form of malls and trade centers. The focus of this research is how are modern retail business practices and how is consumer protection in modern retail businesses?. The data in this study were collected using the methods of observation, interviews and documentation. This type of research is an empirical juridical research using a socio legal approach. The results in this study are first, modern retail business which is a development of traditional retail. In practice, the business applies modern concepts by utilizing technology and accommodates lifestyle developments at the community and consumer level. However, there are still frequent price mistakes made by business actors to consumers. This starts from the unsynchronized price listed on the displayed product with the price stored in the computerized system (product data input on the computer application) at the cashier. Second, business actors need to make efforts to synchronize prices so that price errors do not occur, as well as pay attention to the total purchases that are calculated automatically by the computerized system (product data input on computer applications) and the money that consumers give. Buyers as consumers get protection under the Consumer Protection Act and khiyar aibi in Islamic law. Increasing the accuracy and accuracy of modern retail business actors must always be done, and consumers are required to be smarter in this contemporary muamalah era, by understanding a good transaction method to avoid unwanted things.